Uso de sistemas de informação geográfica no estudo de idosos em situação de risco - Costa, Vera Regina Pontrémoli (2011)
This study had the main aim of identifying and analyzing the bad treatments against elderly into the urban limits of the city of Santa Maria / RS, Brazil. Strictly, it meant: placing the relation among existence, frequency, location and types of domestic violence against elderly; identifying the levels of vulnerability to bad treatment cases reported in the police in a department called Policy of the Elderly; and charting the levels of the amount of elderly in risk through geo information. In order to contribute with the process of the analyses of the bad treatments in a more dynamic way, it was used the geomatics because this area of knowledge gives priority to the multidisciplinary, motivating to perform works by using and developing the information technology. In order to reach the proposed aims, a survey in the termination services like Accident Report (AR) was done in the Police of the Elderly in terms of the years 2007/2008. After getting the information, the following categories were established: age, genre, marital status, neighborhood, victim s literacy and profession besides the type of reported aggression, relation aggressed and aggressor. Possessing that information, it was done a cadastral map placing the aggressors in the city what gives origin to the listed categories. For this, it was used the GIS and the computer program ARCVIEW 9, 3. The database is the table of Attributes for ARCVIEW 9, 3 organized by the Excel table. Each column has a field with spatial and non spatial data that were interrelated allowing visualization. In a whole, 350 chips were analyzed but 138 of them were excluded because they did not fit with the aim of the study. It was observed in the study that from those 212 chips that were investigated for bad treatments against elderly, 92 (44%) lived with the partner. According to WHO (2007), almost half of all women murdered are killed by partner or boyfriend. The majority of the elderly have basic education (63.21%), following by High School (9.43%) scoring 72.64%. Considering some years ago education was not as accessible as it is nowadays, that datum is completely justified. The female genre between 70 to 79 years old was what presented higher levels of bad treatments, scoring 63 women. Married women and widows presented the highest levels. Analyzing the type of aggression, this study verified that the physical aggression happens with more frequency, following by psychological (threats) ones and bad treats. From the 42 neighborhoods into the urban limits of the city of Santa Maria RS, it was verified that the largest concentration of bad treatments against elderly is placed in the neighborhoods: center with 22 complaints; Camobi with 17 complaints; Passo da Areia with 15 complaints. Among the aggressors, 83 were sons, 24 were daughters and 19 were victim s neighbors. Relating the indexes presented by the Police of the Elderly, it is important to clarify that they do not represent the whole amount of the bad treatments there are in our society. There are elderly who do not denounce the violence, the aggressions and the contempt situation in which they live.